Pengaruh Service Quality, Customer Satisfaction dan Switching Cost terhadap Customer Loyalty (Studi pada Pelanggan Telepon Bergerak di Kota Malang) - Abdurrahman, Taufiq; Suryadi, Nanang (Jurnal Aplikasi Manajemen, 2009)
For last few decades we have witnessing the rise of mobile telecommunication industries in Indonesia. High tension level of competition has forced service providers to formulate way both to gain profit and to make their customer stay loyal. Each provider competing through their quality and their price since the Indonesian market were sensitive to price. Many promotional advertising were made in order to attract new customers and make existing customers remain loyal. Theoretically satisfactions were proved affecting customer loyalty. This research was made to identify whether Service Quality, Customer Satisfaction and Switching Cost could affect the Customer Loyalty.